Efektivitas Relaksasi Teknik Meditasi untuk Membantu Siswa Mengatasi Stres sebelum Menghadapi Ujian Nasional - Dosi Juliawati; Rinda Tri Ayumi; Hengki Yandri; Alfaiz Alfaiz (Indonesian Journal of Learning Education and Counseling, 2019)
Research purpose is for reveal the effectivity of relaxation with meditation technique for helping releasing a student’s stress before national examination. Quantitative analysis was using in this research with pre-experiment through one group pretest-posttest design with twelve respondent that has been indentified a stress condition through instrumentation with likert scale. Data analyse with wilcoxon and descriptive. The result was found that there was a significant difference about the level of student’s stress before a national examination and after has given an intervention such a relaxation with meditation technique with asympthotic significant two tailed 0.000. This research can be conclude that relaxation with meditation technique can reduce student’s condition of stress to face a national exam.